PROSPECTIVE STUDY OF ANALYSIS OF OCULAR MANIFESTATIONS OF BLUNT TRAUMA TO THE EYE - Dr.M.Jeevitha , Dr.T.Udaya kumar, Dr.V.S.Saravanan, Dr Arun Kumar Mohan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Ocular blunt trauma is one of the major yet avoidable causes of monocular blindness throughout the world. As seen from study data, the people of the most active and productive age groups were involved in occupational hazards and RTA, which leads to visual impairment, cosmetic disfigurement and serious economic loss to the community. Males are commonly injured in RTA which is probably related to both exposure and risk-taking behavior.